Patient-reported outcomes of arthroscopic rotator cuff repair with biceps tenodesis versus arthroscopic isolated rotator cuff repair: A prospective cohort study - AlAdraii, Adnan Ahmed Saleh; Al Malki, Khalil Awad; Alzahrani , Moroj Mohammed; Rajab , Alya Majed; Al mutairi , Saud Mamdouh; Isa , Hussam Ishag; Mohorjy , Doaa Khalid; Al-Dubai , Sami Abdo Radman (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The long head of the biceps (LHB) tendon is associated with rotator cuff pathology. Combined LHB tenodesis and arthroscopic rotator cuff repair (RCR) improves patient function. This study aimed to compare the patient-reported outcomes of arthroscopic RCR with versus without LHB tenodesis.Methods: This prospective cohort study compared the patient-reported outcomes of American Shoulder and Elbow Surgeons (ASES) scores and University of California at Los Angeles Shoulder Rating (UCLA) scores of patients with complete rotator cuff tears who underwent RCR with or without LHB tenodesis. The study included 102 patients, of whom 66 (64.7%) underwent arthroscopic RCR with LHB tenodesis (biceps tenodesis group) and 36 (35.3%) underwent RCR without LHB tenodesis (non-biceps tenodesis group). Patients were evaluated at 3, 6, 9, and 12 months postoperative.Results: The mean (standard deviation) patient age was 54.5 (9.8) years. Patients in the biceps tenodesis group did not show significantly greater improvement at the 12-month follow-up than those in the non-biceps tenodesis group (mean ASES score, 41.32 vs. 39.96; P < 0.001; mean UCLA score, 12.35 vs. 11.59; P < 0.001). ASES and UCLA scores increased significantly over the study in both groups. There were no significant intergroup differences in either score during the study, indicating equal procedural performance.Conclusions: ASES and UCLA scores increased significantly over the study but did not differ significantly between groups. This study demonstrated that routine arthroscopic RCR with LHB tenodesis has no additional benefit over RCR without LHB tenodesis.